Robust Reduced Multiple-Model Control Algorithm for Type 1 Diabetic Patients - Rikhtehgar, Pouya; Haeri, Mohammad (Conference proceedings - Canadian Conference on Electrical and Computer Engineering, 2024)
Type 1 diabetes mellitus (T1DM) systems present a significant challenge for control due to their complexities. While multiple model and model order reduction techniques offer promising solutions, ensuring stability can be difficult. This study proposes a novel algorithm that addresses the robust stability concern via Lyapunov approach.